2019
DOI: 10.35741/issn.0258-2724.54.4.27
|View full text |Cite
|
Sign up to set email alerts
|

Review of Dependability Assessment of Computing System with Software Fault-Injection Tools

Abstract: The importance of systems dependability is the main motivation for developing fault injection methods (because fault injection is one of the most important ways to assess system dependability). Dependability assessment automatically generates mathematical models of reliability based on simple representations of the parameters of the functions of the system components, service and logistics functions, subsystem order structures, and critical functions. If necessary, it is also possible to develop a detailed mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Because the process of injecting a real error or fault is very expensive for computer parts of software and hardware, we have relied on learning of open-source software and their preparations to receive faults and predict them through these faults reports in the event that one of these errors/faults target the systems really during the system execution period. Through the process of research and study of tools previously built to inject faults that were published in our review of related works [8], there was a need to build a new injection tool through which we can inject faults to an integrated system that includes an operating system, a web browser, database software, and the web language software.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the process of injecting a real error or fault is very expensive for computer parts of software and hardware, we have relied on learning of open-source software and their preparations to receive faults and predict them through these faults reports in the event that one of these errors/faults target the systems really during the system execution period. Through the process of research and study of tools previously built to inject faults that were published in our review of related works [8], there was a need to build a new injection tool through which we can inject faults to an integrated system that includes an operating system, a web browser, database software, and the web language software.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Through studying and analyzing the reviews and publications on the subject of this project in [8], we found that faults injection is a confirmed and significant method for assessment of software dependability. To inject faults, researchers and developers have created several new techniques that can be performed in hardware, software, or both.…”
Section: Introductionmentioning
confidence: 97%
“…Financial literacy allows a person not to be dependent on circumstances, the will of other people, or the system. An educated person himself can choose the paths in life that will be most attractive to him, creating the material basis for the further development of society" (Zelentsova, Bliskavka and Demidov, 2012;Caplinska & Ohotina, 2019;Abd & Behadili, 2019).…”
Section: Introductionmentioning
confidence: 99%